Persistence of IgG COVID-19 antibodies: A longitudinal analysis - Carvalho, Álvaro; Henriques, Ana Rita; Queirós, Paula; Rodrigues, Joana; Mendonça, Nuno; Rodrigues, Ana Maria; Canhão, Helena; de Sousa, Germano; Antunes, Francisco; Guimarães, Miguel (Frontiers in Public Health, 2023)
Background and aim The kinetics of antibody production in response to coronavirus disease 2019 (COVID-19) infection is not well-defined yet. This study aimed to evaluate the antibody responses to SARS-CoV-2 and its dynamics during 9-months in a cohort of patients infected during the first phase of the pandemic. As a secondary aim, it was intended to evaluate the factors associated with different concentrations of IgG antibodies. Methods A prospective cohort study was conducted from June 2020 to January 2021. This study recruited a convenience sample of adult individuals who where recently diagnosed with COVID-19 and were living in mainland Portugal. A total of 1,695 blood samples were collected from 585 recovered COVID-19 patients up to 9 months after SARS-CoV-2 acute infection. A blood sample was collected at baseline and three, 6 and 9 months after SARS-CoV-2 acute infection to assess the concentration of IgG antibody against SARS-CoV-2. Results The positivity rate of IgG reached 77.7% in the first 3 months after symptom onset. The IgG persists at all subsequent follow-up time-points, which was 87.7 and 89.2% in the 6th and 9th months after symptom onset, respectively. Three distinct kinetics of antibody response were found within the 9 months after infection. Kinetic 1 (K1) was characterized by a constant low IgG antibody concentration kinetic (group size: 65.2%); kinetic 2 (K2), composed by constant moderate IgG kinetic (group size: 27.5%) and kinetic 3 (K3) characterized by higher IgG kinetic (group size: 7.3%). People with ≥56 years old (OR: 3.33; CI 95%: [1.64; 6.67]; p-value: 0.001) and symptomatic COVID-19 (OR: 2.08; CI 95%: [1.08; 4.00]; p-value: 0.031) had higher odds of a “Moderate IgG kinetic.” No significant association were found regarding the “Higher IgG kinetic.” Conclusion Our results demonstrate a lasting anti-spike (anti-S) IgG antibody response at least 9 months after infection in the majority of patients with COVID-19. Younger participants with asymptomatic disease have lower IgG antibody positivity and possibly more susceptible to reinfection. This information contributes to expanding knowledge of SARS-CoV-2 immune response and has direct implications in the adoption of preventive strategies and public health policies.